Do birds of different feather flock together? Analyzing the political use of social media through a language-based approach in a multilingual context. (September 2018) - Ahmed, Saifuddin; Jaidka, Kokil; Cho, Jaeho
Abstract: This study analyzes the political use of Twitter in the run-up to the 2013 Malaysian General Election. It follows a content and social network analysis approach to investigate the interplay of language and political partisanship in social media use, among Twitter users in Malaysia. In the period leading up to the 2013 elections, Twitter posts collected under the hashtag #GE13 reveal that communities that post in English versus the Malay language, differ in how they use Twitter and with whom they interact. As compared to English users, Malay users are more likely to seek political information and express their political opinion. In online discussions, we observe language-based homophily within the English and Malay language communities, but there are some cross-cutting interactions between opposing political communities. We discuss the implications of our findings for the political use of new communication technologies in multi-ethnic and multilingual societies. Highlights: The study analyzes the political use of Twitter during the 2013 Malaysian GE. Malay and English language communities differed in their Twitter use. Malay users seek political information and express their political opinion. English language users share and disseminate more information. Both homophily (language) and cross-cutting interactions (partisanship) are found.